Peranan Ilmu Komputer Dalam Perhitungan Uji Beton Di Laboratorium - Marwahyudi, Marwahyudi (Gaung Informatika, 2011)
Sugar  factory waste  is pretty exciting stuff  for  in  the analysis. Waste generated  solid, gas, liquid still need to utilize the waste handling. On this occasion, the researcher tried to analyze molasses added to concrete materials. In this study, we created two groups of specimens will be  compared to  the results which one is better. Then  the object  tested sectioned with a compression  test machine. After investigation  it  turned out  the result showed  the difference between concrete with molasses added material would be better than  ordinary concrete.  Top  Calculation results  divisive  15.63  Kg/cm2  test  without added ingredients and 33.71 Kg/cm2 concrete with molasses added ingredients.